Palm Tree Coplanar Vivaldi Antenna Array on the Same Substrate Size: Design and Performance Evaluation - Nurhayati, Nurhayati; De Oliveira, Alexandre Manicoba; Yasin, Mohd Najib Bin Mohd; Kurniawan, Dayat (International Journal of Electronics and Communications Systems, 2022)
This paper aims to describe the performance of the palm tree Coplanar Vivaldi Antenna Array (CVA) that was simulated from 0.25-6.25 GHz in terms of return loss and radiation pattern. Palm Tree Coplanar Vivaldi Antenna is available in four different configurations: single-element, two-element array, four-element array, and an eight-element array. We create a feeding network and radiator patch for two, four, and eight-array antennas. The simulation results demonstrate that the single-element antenna has the best return loss performance and can cover all frequency work from 0.25-6.25 GHz. In contrast, the antenna array can only cover multiband frequency. At 3 GHz, a single-element antenna has a directivity of 8.77 dBi, a sidelobe level of -2.2 dB, and a beamwidth of 63.70. In contrast, an antenna array of 8 elements has a directivity of 15.5 dBi, a sidelobe level of -12.6 dB, and a beamwidth of 80. Using the same substrate size, by configuring the Vivaldi Coplanar antenna to be an array at a frequency of 3 GHz, the 1×8 array antenna has a 6.73dBi improvement in directivity, a 10.4 dB boost in side lobe level, and a 55.70 enhanced in beamwidth performance compared to a single element. According to the simulation findings, the radiation pattern performance of the. Palm Tree CVA is greater than a single element in the same substrate size. Good directivity, SLL, and beamwidth performance make the proposed Palm Tree CVA array suitable for integration in telecommunication, radar, or cognitive radio applications.